2017
DOI: 10.1016/j.neubiorev.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion perception in patients with epilepsy: A systematic review with meta-analysis

Abstract: Facial emotion perception is a fundamental social competency relying on a specialised, yet distributed, neural network. This review aimed to determine whether patients with epilepsy have facial emotion perception accuracy impairments overall, or for a subset of emotions (anger, disgust, happiness, sadness, fear, and surprise), and the relationship to epilepsy type, demographic/treatment variables, and brain organisation. Database searches used PRISMA guidelines with strict inclusion/exclusion criteria. Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 95 publications
3
24
1
2
Order By: Relevance
“…Similarly to the findings in our study, one report found no difference in empathy and ER tasks between TLE and GGE, and another presented post hoc results revealing worse performance among PWE with focal epilepsies as opposed to HC or patients with GGE [4,6]. Overall, no difference is found in facial emotion perception between the two epilepsy subgroups [6,[22][23][24]. Investigations of SC in focal epilepsies alone are more frequent-authors of a recent review of 42 studies concluded that no significant variation exists between patients with TLE and ETE in ER and ToM tasks, which is in line with our findings [25].…”
Section: Relationships and Quality Of Lifesupporting
confidence: 88%
“…Similarly to the findings in our study, one report found no difference in empathy and ER tasks between TLE and GGE, and another presented post hoc results revealing worse performance among PWE with focal epilepsies as opposed to HC or patients with GGE [4,6]. Overall, no difference is found in facial emotion perception between the two epilepsy subgroups [6,[22][23][24]. Investigations of SC in focal epilepsies alone are more frequent-authors of a recent review of 42 studies concluded that no significant variation exists between patients with TLE and ETE in ER and ToM tasks, which is in line with our findings [25].…”
Section: Relationships and Quality Of Lifesupporting
confidence: 88%
“…It is also observed how the presence of certain pathologies such as ADHD, BPD, epilepsy, depression, alcoholism, schizophrenia, psychopathy, etc., influence the recognition of emotions through facial expressions, the authors conclude that regardless of the disease that the person analysed in this article is suffering from, their level of assertiveness and interpretation is lower compared to a healthy person (Cortez et al, 2017;Domes et al, 2009;Edwards et al, 2017& Pham, 2010.…”
Section: Discussionmentioning
confidence: 90%
“…Four prior meta-analyses evaluated theory of mind and emotion recognition among patients with epilepsy and outcomes slightly differ depending on the groups of patients studied or the outcome measures. Overall, these studies reveal several findings: (a) theory of mind ability was mostly affected among patients with focal seizure such as frontal lobe epilepsy (FLE) and temporal lobe epilepsy (TLE), but not outside these areas (extra-TLE/FLE; Stewart et al, 2016); (b) deficient recognition of fear, followed by sadness and disgust, among patients with epilepsy across both visual and auditory modalities have been reported (Edwards et al, 2017; Monti et al, 2015); (c) the right-sided TLE patients exhibited more significant impairments recognizing fear, disgust, and sadness compared to left-sided TLE (Bora et al, 2016); (d) and lastly, surgery did not change the social cognitive outcomes (emotion recognition and theory of mind) relative to the groups who did not undergo surgery (Bora et al, 2016).…”
Section: Introductionmentioning
confidence: 90%